A study on glycemic control and related complications in type I diabetic children - Dr Alkarani T Patil; Dr Rajashekara Murthy G R; Dr Hema G R (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Type I Diabetes Mellitus is a common, chronic, metabolic syndrome characterized by hyperglycaemia as a cardinal biochemical feature. Patients with diabetes mellitus face an increased risk of morbidity and mortality due to micro and macrovascular complications caused by diabetes. There is lack of Indian studies on diabetic children. Hence this study was undertaken to know glycaemic control and related complications in type I diabetes mellitus.Materials and methods: This is a Prospective study conducted in Diabetic Clinic at Indira Gandhi institute of Child Health, Bengaluru for 1 year. Study group had 34 diabetic children; they were followed up for period of one year to assess glycaemic control and complications of the disease.Results: 34 children were followed up for a period of one year to study glycaemic control and related complications. Glycaemic control was assessed using HbA1c. Seven children had good and 27 had poor glycaemic control. Factors associated with poor glycemic control were analyzed. Age at onset of the disease more than 12, duration of disease more than 5 years, female children in pre-pubertal age were associated with poor control. Children were followed up for development of complications. 4 children presented with DKA (11.76%), 12 had hypoglycaemia (35.29%).Conclusion: Poor glycaemic control was associated with longer duration of disease, female sex and disease being diagnosed in pubertal period.